Avian Diversity as a basis for developing Birdwatching Ecotourism in the Industrial Landscape of PT Indonesia Asahan Aluminium (PT Inalum), North Sumatra, Indonesia - Pradana, Gilang; Putra, Chairunas Adha (JURNAL BIOSAINS, 2026)
Industrial landscapes are often perceived as degraded environments with limited ecological value. However, when managed responsibly, such areas can contribute to biodiversity conservation and environmental education. This study investigated the diversity, conservation status, and ecotourism potential of birds in the operational areas of PT Indonesia Asahan Aluminium (PT Inalum), located in Batu Bara Regency, North Sumatra. Bird surveys were conducted from August 2023 to May 2024 across three habitat types: residential green areas, plantation and shrub habitats, and coastal–mudflat zones. Data were collected through direct visual observations, supported by photographic documentation and sound recordings. Species identification followed Eaton et al. (2021), and conservation status was assessed using the IUCN Red List and Indonesian national protection regulations. A total of 103 bird species belonging to 41 families were recorded. Of these, 22 species are legally protected in Indonesia, and one species is listed as Endangered globally, the Milky Stork Mycteria cinerea. The study also documented 31 migratory species and several breeding records, including Nisaetus Limnaeetus, Pycnonotus analis, Treron vernans, Ploceus philippinus, and Merops philippinus, indicating the site’s importance for both resident and migratory populations. The diversity and breeding activity suggest that PT Inalum’s managed habitats provide suitable ecological conditions for birds despite industrial operations. These findings demonstrate that corporate-managed lands can serve as complementary conservation habitats and highlight their potential for birdwatching-based ecotourism and environmental education. Establishing a continuous monitoring program, strengthening wildlife management capacity, and developing interpretive facilities are recommended to enhance conservation outcomes and promote sustainable industry biodiversity integration.